2020
DOI: 10.15253/2175-6783.20202142980
|View full text |Cite
|
Sign up to set email alerts
|

Progressão do cateter central de inserção periférica em região hemiclavicular de recém-nascidos

Abstract: Objetivo: avaliar a progressão do cateter central de inserção periférica em região hemiclavicular direita, através da veia basílica e cefálica direita, em recém-nascidos. Métodos: pesquisa quase experimental, realizada em unidade neonatal. Amostra de 64 inserções de cateteres, em 58 recém-nascidos. A intervenção consistiu em manobra de elevação, protração e abaixamento do ombro, aplicada após não progressão do cateter, em região hemiclavicular, na punção direta em região cubital, em veia basílica ou cefálica d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 7 publications
1
13
0
5
Order By: Relevance
“…The selected scientific articles allowed the detailed identification of the following maneuvers used in cases of nonadvancement of the CVC: abduction of the arm for insertion of the catheter at 90°; infusion of saline solution during the insertion of the catheter; head-turn supraclavicular pressure maneuver; shoulder elevation, protraction, and lowering (EPL) maneuver; anterior rotation of the shoulder with downward traction; internal rotation of the arm with upward pressure on the scapula; increased contralateral rotation of the head; twisting the head of the patient to the side of the vein; direct finger pressure on the ipsilateral internal jugular vein directly above the jugular notch; continuous Valsalva maneuver; ipsilateral shoulder elevation; twisting the head to the side of the vein that has been catheterized; and downward traction on the ipsilateral arm. Five articles in this review revealed the difficulty of catheter advancement 3,[12][13][14][15] for peripheral central insertion. One study addressed the central venous route, indicating that the catheter can be positioned in the central position, through both the central and peripheral routes.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The selected scientific articles allowed the detailed identification of the following maneuvers used in cases of nonadvancement of the CVC: abduction of the arm for insertion of the catheter at 90°; infusion of saline solution during the insertion of the catheter; head-turn supraclavicular pressure maneuver; shoulder elevation, protraction, and lowering (EPL) maneuver; anterior rotation of the shoulder with downward traction; internal rotation of the arm with upward pressure on the scapula; increased contralateral rotation of the head; twisting the head of the patient to the side of the vein; direct finger pressure on the ipsilateral internal jugular vein directly above the jugular notch; continuous Valsalva maneuver; ipsilateral shoulder elevation; twisting the head to the side of the vein that has been catheterized; and downward traction on the ipsilateral arm. Five articles in this review revealed the difficulty of catheter advancement 3,[12][13][14][15] for peripheral central insertion. One study addressed the central venous route, indicating that the catheter can be positioned in the central position, through both the central and peripheral routes.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the shoulder and clavicle must be healthy and without fractures or dislocation so that the movement of the joint does not cause injury (Figure 2). 3 These analyses indicate that difficult catheter advancement may occur in both peripheral and central veins in adult, pediatric, and neonatal patients. The explanation for this phenomenon is that the catheter does not advance due to anatomic venous imperfections, narrow angles between the central vessels, venous spasms, and obstructions.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations